Perencanaan Arsitektur Enterprise Dengan Kerangka Kerja TOGAF (The Open Group Architecture Framework) Pada PT. Puma Logistics Indonesia - Latjuba Sofyana STT (INFORMAL: Informatics Journal, 2017)
PT Puma Logistic Indonesia is a company which dwelled in freight forwarder services. In carrying out its business activities, the company still use manual processes, Manual data management will present a lot of risks, including simple errors in recording or data input. Therefore, PT Puma Logistics Indonesia requires need information technology and system that could support and manage the company’s business process well. Based on these problems, the PT Puma Logistics Indonesia requires enterprise architecture planning. The results in this study indicate enterprise architecture planning using TOGAF ADM can produce models of enterprise architecture (blueprint) that can be used as a guide in the procurement and development of IS / IT at PT. Puma Logistics Indonesia. The blueprint includes 13 business functions in a business process architecture, 27 new entities in the architecture of the data, four application modules at the application architecture and the provision and upgrading of hardware and software in the PT. Puma Logistics Indonesia in architectural technology.